IDENTIFIKASI DAN ANALISA RISIKO KECELAKAAN KERJA DENGAN METODE FMEA (FAILURE MODE AND EFFECT ANALYSIS) PADA KELOMPOK TANI PALAS BARU RUMBAI - Putri Permata Yanda; Herniwanti Herniwanti; Makomulamin Makomulamin (STIKes Al-Insyirah Pekanbaru, 2020)
A preliminary survey conducted by the author in early 2019 was randomly simple on farmer groups in the Village of Maharani District of Rumbai, each of 3 farmers, obtained information that farmers do not know and understand and apply OHS in their work. Farmers do not have work procedures, especially when using various types of agricultural equipment. Therefore this study aims to determine the source of work accident risk. Referring to the JSA AS / NZS: 4360 Risk Management concept and the FMEA method. The research design carried out was observational analytic. Data collection was obtained from observations and in-depth interviews. The results of observations and in-depth interviews with informants revealed five risks at each stage of the agricultural process, in this case, chili planting including the preparation of agricultural land with the risk of injury due to a sharp hoe component RPN 27 is at a Very High-risk level. The risk of itching and water lice at the stage of planting RPN 8 is a high-risk level, the risk of wounds caused by sickles when maintaining RPN 18 is a high-risk level. Being absorbed by chemicals when controlling RPN 18 levels of risk High and risk of being attacked by venomous animals RPN 8 Medium risk level in the harvest process, advice for farmer groups must be more active in raising awareness of OHS, and also for relevant agencies to pay attention to OHS especially health services and agriculture in the working area of ​​Rumbai Bukit District.